[tex]A=(0,1); \ \ \ B=(1,0)[/tex]
y = ax+b
[tex]\pmb{1^{o}} \\ \\ \begin{cases} 1 = 0*a + b \\ 0 = 1*a + b \end{cases} \\ \\ \begin{cases} b = 1 \\ a+b = 0\end{cases} \\ \\ \begin{cases} b = 1 \\ a+1 = 0 \end{cases} \\ \\ \begin{cases} b = 1 \\ a = -1 \end{cases} \\ \\ \\ y = -x +1 \\ \\ y+x = 1 \\ \\ \boxed{4y+4x = 4}[/tex]
[tex]\pmb{2^{o}} \\ \\ If \ A=(x_{1}, y_{1}); \ \ \ B = (x_{2},y_{2}) \\ \\ (x_{2} - x_{1}) (y - y_{1})=(y_{2}-y_{1})(x -x_{1}) \\ \\ (1 - 0)(y - 1)=(0 - 1)(x - 0) \\ \\ y - 1 = -x \\ \\ y+x = 1 \\ \\ \boxed{4y+4x = 4} [/tex]